Endometrial ablation and resection versus hysterectomy for heavy menstrual bleeding: an updated systematic review and meta-analysis of effectiveness and complications - Clare Deehan; Iliana Georganta; Anna Strachan; Marysia Thomson; Miriam McDonald; Kerrie McNulty; Elizabeth Anderson; Alyaa Mostafa (Korean Society of Obstetrics and Gynecology, 2023)
To evaluate the clinical efficacy, safety, and cost-effectiveness of endometrial ablation or resection (E:A/R) compared to hysterectomy for the treatment of heavy menstrual bleeding. Literature search was conducted, and randomized control trials (RCTs) comparing (E:A/R) versus hysterectomy were reviewed. The search was last updated in November 2022. Twelve RCTs with 2,028 women (hysterectomy: n=977 vs. [E:A/R]: n=1,051) were included in the analyzis. The meta-analysis revealed that the hysterectomy group showed improved patient-reported and objective bleeding symptoms more than those of the (E:A/R) group, with risk ratios of (mean difference [MD], 0.75; 95% confidence intervals [CI], 0.71 to 0.79) and (MD, 44.00; 95% CI, 36.09 to 51.91), respectively. Patient satisfaction was higher post-hysterectomy than (E:A/R) at 2 years of follow-up, but this effect was absent with long-term follow-up. (E:A/R) is considered an alternative to hysterectomy as a surgical management for heavy menstrual bleeding. Although both procedures are highly effective, safe, and improve the quality of life, hysterectomy is significantly superior at improving bleeding symptoms and patient satisfaction for up to 2 years. However, it is associated with longer operating and recovery times and a higher rate of postoperative complications. The initial cost of (E:A/R) is less than the cost of hysterectomy, but further surgical requirements are common; therefore, there is no difference in the cost for long-term follow-up.